Implementation on the Referral System of High Risk Pregnant Women from Villages Midwives to Primary Healthcare Center with Basic Obstetric and Neonatal Emergency Care in Banjar District, South Kalimantan (a Case Study in Sungkai Primary Healthcare Center) - Adriana Palimbo; Ayun Sriatmi; Tjahjono Kuntjoro (Jurnal Manajemen Kesehatan Indonesia, 2015)
Kualitas pelayanan rujukan kebidanan tidak bisa terlepas dari system rujukan yang dilaksanakan oleh bidan desa sebagai pos pelayanan terdepan di masyarakat. Selain karena faktor sistem penanganan kasusnya yang kurang sesuai dengan prinsip dasar merujuk, diduga juga karena keterlambatan menganal tanda bahaya dan mengambil keputusan dan terlambat mendapat pelayanan di fasilitas kesehatan. Tujuan penelitian adalah menjelaskan pelaksanaan sistem rujukan ibu hamil risiko tinggi oleh bidan desa ke Puskesmas PONED Kabupaten Banjar tahun 2011. Penelitian ini adalah penelitian observasional menggunakan rancangan deskriptif kualitatif, dalam bentuk studi kasus untuk menggambarkan dan memahami fenomena yang berkaitan dengan pendekatan crossectional. Instrumen penelitian adalah bidan desa Puskesmas Sungkai yang melakukan rujukan kasus ibu hamil risiko tinggi ke Puskesmas PONED. Data dikumpulkan dengan wawancara mendalam dan dianalisis dengan teknik kualitatif. Hasil penelitian menunjukkan bahwa masih ada bidan desa yang melakukan stabilisasi diluar kewenangan. Sebagian besar masyarakat menggunakan pembiayaan Jamkesmas, tetapi dari biaya dan ketersediaan transportasi/ambulan desa dan keperluan lain masih masih kurang memadai bagi pasien Jamkesmas. Selama proses pendampingan bidan sebagian besar hanya mendampingi jika pasien dirujuk ke RS swasta, tetapi hal sama tidak dilakukan pada pasein Jamkesmas. Dalam merujuk ibu hamil ke puskesmas PONED bidan desa tidak membawa surat pengantar rujukan, tetapi hal sama juga tidak dilakukan saat merujuk ke RS swasta. Bidan menyertakan surat dan lampiran buku KIA jika ke RS umum untuk tujuan klem Jamkesmas. Berdasarkan hasil penelitian tersebut disarankan kepada Dinas Kesehatan untuk melengkapi jumlah tenaga bidan desa dan kualifikasinya, serta kecukupan alat/obat/bahan di Polindes/Poskesdes. Bagi Puskesmas untuk melakukan pembinaan dan supervisi bidan di desa dan ada pembagian tugas yang jelas untuk bidan desa di wilayah kerjanya. Quality of obstetrical referral service could not be separated from referral system done by village midwives as a front health service post in the community. Obstetric case management that was not fully follow a basic principle of referral, delays to identify signs of dangerous pregnancy condition, delay to make decision, and delay to obtain services in the health facility were factors related to the quality of obstetrical referral service. The objective of this study was to explain the implementation of high risk pregnancy referral system by village midwives to PONED primary healthcare center Banjar district, 2011. This was an observational study using descriptive qualitative design. This study was in the form of a case study to describe and to comprehend related phenomena using cross sectional approach. Study instrument was village midwives from Sungkai primary healthcare center who referred high risk pregnant women to PONED primary healthcare center. Data were collected by conducting in-depth interview. Qualitative technique was applied to analyze the data. Results of the study showed that village midwives still performed stabilization beyond their authority. Majority of people in the community used Jamkesmas (community health insurance) funding; however, funding and transportation or village ambulance availability and other needs were insufficient for Jamkesmas patients. During midwives accompaniment, most of them only accompanied when the patient was referred to the private hospital, and they did not do that for Jamkesmas patients. Midwives did not bring reference letter to PONED primary healthcare centers when they were referring pregnant women; it was also done when they were referring pregnant women to private hospitals. Midwives included a letter and KIA book as an enclosure when they referred the patient to the general hospital for Jamkesmas claim purpose. Based on the study results, suggestions given to the head of district health office were to provide additional number of village midwives with its qualification; to assure the availability and sufficiency of instrument, medicine and materials in Polindes or Poskesdes; Suggestions for primary healthcare office were to conduct guidance and supervision for village midwives, to distribute clearly the job assignments to village midwives in their work areas.